Simulation of Propagating Acoustic Wavefronts with Random Sound Speed (Communications in Computational Physics, 2014)
A method for simulating acoustic wavefronts propagating under randomsound speed conditions is presented. The approach applies a level set method to solvethe Eikonal equation of high frequency acoustics for surfaces of constant phase, insteadof tracing rays. The Lagrangian nature often makes full-field ray solutions difficult toreconstruct. The level set method captures multiple-valued solutions on a fixed grid.It is straightforward to represent other sources of uncertainty in the input data usingthis model, which has an advantage over Monte Carlo approaches in that it yields anexpression for the solution as a function of random variables.